2021
DOI: 10.1186/s12967-021-03049-0
|View full text |Cite
|
Sign up to set email alerts
|

TFH cells in systemic sclerosis

Abstract: Systemic sclerosis is an autoimmune disease characterized by excessive dermal fibrosis with progression to internal organs, vascular impairment and immune dysregulation evidenced by the infiltration of inflammatory cells in affected tissues and the production of auto antibodies. While the pathogenesis remains unclear, several data highlight that T and B cells deregulation is implicated in the disease pathogenesis. Over the last decade, aberrant responses of circulating T follicular helper cells, a subset of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Tfh, described in the early 2000s, has been shown to localize in B cell follicles with a high expression of CXCR5, 37–39 engages in mediating the activation of B cells, and indirectly stimulates the generation of autoimmune antibodies through the expression of B cell lymphoma 6 (BCL‐6) transcription factor 40 . Morita et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tfh, described in the early 2000s, has been shown to localize in B cell follicles with a high expression of CXCR5, 37–39 engages in mediating the activation of B cells, and indirectly stimulates the generation of autoimmune antibodies through the expression of B cell lymphoma 6 (BCL‐6) transcription factor 40 . Morita et al.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐21, a major Tfh‐related cytokine, can facilitate Th17 cell differentiation and regulate the production of immunoglobulin, resulting in subsequent inflammation caused by Th17 42 . While the contribution of Tfh to the pathogenesis of SSc is unclear enough, the frequency of Tfh in SSc has been inconstantly reported 40 . In our data, compared to HCs, decreased Tfh1 and increased Tfh2 were found in the SSc group, with similar proportions of total Tfh, Tfh17, and activated Tfh with activation marker PD‐1 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Tfh cells exert their functions through auxiliary B cells ( 23 ). It has been suggested that Tfh cells may have granuloma-inducing and pro-liver fibrosis effects ( 24 ). In summary, during the persistence of viral hepatitis, inflammation-associated immune cells were upregulated, and anti-inflammatory immune cells were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…This sort of T cells are usually found in inflamed tissues of secondary lymphoid and non-lymphoid organs and provide auxiliary support to B cells such as stimulating them to produce antibodies ( Hutloff, 2018 ; Yoshitomi and Ueno, 2021 ). It has been reported that such cells are significantly associated with pulmonary fibrosis, skin fibrosis and systemic sclerosis, and that the main mechanism may be related to immune disorders leading to excessive accumulation of antibodies to form inflammatory fibrotic repair after immune damage ( Clark, 2018 ; Beurier et al, 2021 ; Zhang et al, 2021 ). However, it is still very poorly studied in cardiac tissue fibrosis, and only very few studies have reported finding that this cell is associated with the cardiac inflammatory response such as in heart transplants, where it enhances the function of B cells to promote a chronic inflammatory response ( Wang Y. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%